ELECTRONIC AND SOCIAL MARKETING AND ITS ROLE IN SOCIAL LIFE - Hassan Daghwi Obaid (Scholars Digest Publishing, 2025)
Marketing is one of the important activities that humans have practiced to varying degrees through the development of humanity until it has become one of the important concepts that contribute to many fields. The view of marketing has changed in recent years as it is concerned in the first aspect with the flow of services and delivering them to beneficiaries to meet the need, demand and desires and work to satisfy them through exchange processes at the same time providing various services to solve social problems.
Keywords: Social Marketing, Electronic Marketing, World Wide Web.